The Future of International Transactions: How AI is transforming Cross-Border Payments - Vinod Upputuri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative impact of Artificial Intelligence (AI) on cross-border payment systems, examining how AI technologies are revolutionizing various aspects of international financial transactions. The article delves into AI’s role in enhancing fraud detection through advanced pattern recognition and real-time anomaly detection, significantly improving security measures. It analyzes how AI accelerates payment processing by automating verification and settlement processes, leading to dramatic reductions in transaction times. The article also investigates AI’s contribution to regulatory compliance, discussing how it aids in navigating complex international financial regulations and mitigates risks. Furthermore, it examines the improvement in customer experience through AI-powered chatbots and virtual assistants, offering 24/7 support and personalized service. The optimization of currency exchange using AI algorithms for market trend analysis and exchange rate prediction is also explored. Finally, the article addresses future prospects, potential advancements, ethical considerations, and integration challenges associated with AI in cross-border payments, providing a comprehensive overview of this rapidly evolving field in global finance.